AN ANALYSIS OF FEAR OF MISSING OUT (FOMO) AS A DRIVER OF HOAX DISSEMINATION IN THE PRABOWO ERA USING MLP - Irfan Saputra; Agustina Heryati; Hendra Di Kesuma (Jurnal Kecerdasan Buatan dan Teknologi Informasi, 2026)
The development of social media over the past decade has accelerated the spread of information, including hoaxes, which impact public perception and political stability. One psychological factor contributing to the impulsive spread of information is Fear of Missing Out (FOMO), defined as the feeling of anxiety experienced when individuals believe they are missing important information or events. This study aims to analyze the relationship between the FOMO phenomenon and the tendency to spread political hoaxes related to the Prabowo administration on social media. The research data was obtained through comment crawling techniques on the TikTok platform and then processed using the following stages: preprocessing text (e.g., cleaning, case folding, tokenizing, filtering, stemming) and labeling of FOMO, Non-FOMO, Hoax, and Non-Hoax classes. The Multi-Layer Perceptron (MLP) model is used to classify user behavior patterns. FOMO plays a role in increasing the spread of fake news in the political sphere, and this demonstrates that a combination of psychological factors and machine learning techniques can help understand the dynamics of disinformation on social media.